ECOLITERACY PADA ANAK USIA 5-6 TAHUN - Masyunita Siregar; Sri Martini Meilanie; Agung Purwanto (FIP Unimed, 2020)
ABSTRACTEcoliteracy needs to be given to children from an early age, to reduce various environmental problems caused by humans. For this reason ecoliteration needs to be considered in early childhood, especially children aged 5-6 years. This research is a literature study by examining literature from various sources such as articles from journals, books and scientific works. The results of the study indicate that the age of 5 years is a good start to introduce ecoliteration in children. Children who have ecoliteration or ecological literacy will become a generation that can be responsible for the surrounding environment. Keyword: Ecoliteracy, Early ChildhoodABSTRAKEcoliteracy perlu diberikan kepada anak sejak usia dini, untuk memgurangi berbagai masalah lingkungan yang disebabkan oleh manusia. Untuk itu perlu memahami ecoliteracy pada anak usia dini, khususnya anak usia 5-6 tahun. Penelitian ini merupakan penelitian studi literatur dengan menelaah literatur dari berbagai seumber seperti artikel dari jurnal, buku dan karya ilmiah. Hasil studi menunjukkan bahwa usia 5 tahun adalah awal yang bagus untuk mengenalkan ecoliteracy pada anak. Anak yang memiliki ecoliteracy atau melek ekologi akan menjadi generasi yang dapat bertanggung jawab dengan lingkungan sekitarnya. Kata Kunci: Ecoliteracy, anak usia dini.